Potential of Green Gold Nanoparticles Synthesized from Punica granatum Extract on Leishmaniasis and Breast Cancer Treatment - Kelleci, Kubra (WILEY-V C H VERLAG GMBH, 2025)
In the current study, the physicochemical properties and biological activities of gold nanoparticles (AuNP) synthesized in small sizes by Punica granatum using the green synthesis method and the chemical method were compared. UV-vis peak of chemically and biologically synthesized AuNPs was confirmed at 540 nm and 535 nm, respectively. By FT-IR analysis, it was revealed that there were active biomolecules in Punica granatum extract for the synthesis of green AuNPs. According to XRD results, broad spectra were obtained. The crystalline nature of Green AuNP was demonstrated. Using SEM and DLS, it was observed that green AuNP had dimensions between 4-6 nm and chemical AuNP had dimensions between 6-12 nm. Punica granatum-based AuNPs were more effective in the MDA-MB-231 breast cancer cell line than AuNPs by chemical method. It has also been revealed that green AuNPs are much more effective than chemical AuNPs against L. infantum parasites. As a result, Punica granatum-based green AuNPs have been proven to be functionally more efficient and effective than chemically prepared AuNPs. Our study will encourage researchers to increase the synthesis of green NPs for medical use.
Keywords: Anticancer; Antileishmanial; Gold nanoparticles; Green nanoparticle; Punica granatum; Chemistry